Evaluation of immune protection of a multi-antigenic DNA vaccine encoding TgROP6 and TgMIC12 against Toxoplasma gondii infection - Xu, Bohuai; Bi, Yue; Wang, Yaowen; Sun, Jie; Chen, Jia; Mu, Jingqi (Frontiers in Veterinary Science, 2025)
IntroductionToxoplasma gondii infection causes severe congenital disease and abortion in humans and animals. This study evaluated a novel multivalent DNA vaccine targeting ROP6, and MIC12 for protection against acute (RH strain) and chronic (PRU strain) toxoplasmosis in mouse models.MethodsEukaryotic plasmids encoding pVAX-ROP6 and pVAX-MIC12 were constructed, and mice were immunized with either single or combined formulations.Results and discussionVaccination elicited a robust Th1-biased immune response, characterized by elevated IgG2a/IgG1 ratios, enhanced cytotoxic T lymphocyte activity, increased CD4+ and CD8+ T cell populations, and elevated production of IFN-γ, IL-12, and IL-2. The dual vaccine demonstrated superior efficacy, significantly prolonging survival following lethal RH challenge (compared to uniform mortality in controls by day 6) and reducing PRU brain cyst burden by 56.6%, outperforming single-gene formulations. Although these results establish pVAX-ROP6/MIC12 as promising vaccine candidates, protection remained partial, highlighting the need for further optimization. Overall, this study underscores the potential of bivalent DNA vaccines to induce broad protective immunity against toxoplasmosis, supporting their continued development for clinical and veterinary use.